Study of serum antibodies against three eye muscle antigens and the connective tissue antigen collagen XIII in patients with Graves' disease with and without ophthalmopathy: correlation with clinical features - Gopinath, Bamini; Musselman, Reilly; Adams, Cherie-Lee; Tani, Junichi; Beard, Nicole; Wall, Jack R (Thyroid (New York, N.Y.), 2006)
The extraocular muscles are one of the primary tissues implicated in the autoimmune-mediated inflammation of thyroid-associated ophthalmopathy (TAO). Our aim was to determine the prevalence and level of antibodies against three candidate eye muscle antigens and the orbital fibroblast membrane antigen collagen XIII, in well-characterized patient groups. The study cohort consisted of patients with Graves' hyperthyroidism with and without ophthalmopathy, controls patients with other thyroid or other autoimmune disorders and healthy subjects. The presence of eye muscle antibodies was determined using an optimized and standardized enzyme-linked immunosorbent assay. We measured antibodies against (i) the 67-kDa flavoprotein (Fp) subunit of the mitochondrial enzyme succinate dehydrogenase; (ii) G2s, a 141 amino acid fragment of the winged-helix transcription factor FOXP1; (iii) calsequestrin, a 63-kDa calcium-binding protein; and (iv) collagen XIII, a connective tissue protein that is closely linked to the congestive ophthalmopathy subtype of TAO. Eye muscle antibody levels were correlated with clinical diagnosis and presence or not of ophthalmopathy. Prevalences of positive antibody tests to calsequestrin (75.0%) and collagen XIII (43.8%) were significantly greater in Graves' disease (GD) patients with ophthalmopathy than in healthy subjects, whereas modest significance was demonstrated with antibodies against Fp, but not G2s. Significantly greater serum levels of antibodies against calsequestrin, G2s, and collagen XIII, but not Fp, were found in GD patients with ophthalmopathy compared to control patients without eye disease and healthy subjects. Calsequestrin and collagen XIII antibodies are the most specific to TAO, whereas antibodies against G2s, and to a lesser extent Fp, are also markers of ophthalmopathy, but less reliable. These results are unique in that it is the first time the significance of a panel of three candidate eye muscle antibodies and a connective tissue antibody have been evaluated in the same patients with ophthalmopathy.